CHROMOSOMAL CHARACTERS OF THE INDONESIAN SAND GOBY, OXYELEOTRISMARMORATA BLKR. 1874 (ELEOTRIDAE)*) - JIMMY T. MASAGCA (BIOTROPIA, 1994)
Karyomorphological investigation of sand goby or marble sleeper (Oxyeleotris marmorata Blkr.) from Cirata Reservoir, West Java, Indonesia was undertaken to determine the modal chromosome number and fundamental number, and to construct the karyotype from somatic metaphase cells of head kidney. A total of 30 fish samples from Cirata Reservoir was sacrificed for direct chromosome preparation by colchicine-citrate-aceto-methanol-Giemsa staining-air drying technique. Chromosome set analysis showed that the modal chromosome number of the test fish is 2n = 46, confirming previous studies. Fundamental number is 50. Two karyotypic formulas were found, i.e. 1) 2n = 46 (4SM + 42A); and 2) 2n = 46 (2M + 2SM + 42A). Key Words: Freshwater fishes, Chromosome analysis, Oxyeleotris marmorata, Indonesia